Toward a neurobiology of internal selective attention - van Ede, F; Nobre, AC (Cell Press, 2021)
A recent study in non-human primates (NHPs) by Panichello and Buschman brings the investigation of selective attention within visual working memory to the systems and cellular neuroscience levels. We reflect on this breakthrough in light of nearly 20 years of related research in humans and highlight some of the lessons to help frame future work.